Knowledge: disease process in patients undergoing hemodialysis - de Araújo Ferreira, Jeysse Karla; Ramos Costa Pessoa, Natália; Pereira Pôrto, Nayana; Nóbrega Mendes Santos, Laís; Brandão de Carvalho Lira, Ana Luisa; Farias de Queiroz Frazão, Cecília Maria (Investigación y Educación en Enfermería, 2018)
Objective. To identify the relationship between socioeconomic variables and nursing outcome indicators Knowledge: disease process. Methods. This is a cross-sectional study involving 51 patients undergoing hemodialysis at a public nephrology hospital in a city in northeastern Brazil. A questionnaire covering sociodemographic information and the 15 nursing outcome indicators Knowledge: disease process. Results. A statistically significant but weak correlation was found between age and the indicators Specific process of the disease (r=-0.28), Cause and contributing factors (r=-0.36), Signs and symptoms of the disease (r=0.30), Signs and symptoms of complications of the disease (r=-0.37), Precautions to prevent complications of the disease (r=-0.35); number of years of schooling and the indicators Specific process of the disease (r=0.29), Cause and contributing factors (r=0.28), and Signs and symptoms of the disease (r=0.34). There were significant and moderate correlations of age with the indicator Psychosocial effect of the disease in the individual (r=-0.41), in the family (r=-0.44) and benefits of disease control (r=-0.48). Sex was related only to the indicator Specific process of the disease (p=0.03). Conclusion. There was no relationship between some indicators of the outcome Knowledge: disease process with the sociodemographic variables in patients undergoing hemodialysis, a fact that underscores the importance of implementing nursing interventions that take into account the particularities of the individuals. How to cite this article: Ferreira JKA, Pessoa NRC, Pôrto NP, Santos LNM, Lira ALBC, Frazão CMFQ. Knowledge: disease process in patients undergoing hemodialysis. Invest. Educ. Enferm. 2018; 36(2):e04.